Some historical considerations on the inflammatory theory of atherosclerosis - P. Marson; G. Zanchin; C. Stefanutti (PAGEPress Publications, 2004)
In the past 20 years several clinical and experimental observations have led to the hypothesis that an inflammatory response can trigger some key processes during the development of atherosclerosis. Here we briefly review, from the historical viewpoint, the inflammatory theory of atherosclerosis, as proposed by the Berliner pathologist Rudolf Virchow in the XIX century. Contrary to this hypothesis, in the same period the Viennese Karl von Rokitansky recognized blood dyscrasia (particularly fibrin-induced alterations) as the promoting factor in the process of atherogenesis. Moreover, we outline the relationship between atherosclerosis and arthritis, by reporting some passages from two scientific works published in the late XIX century, the former by the Italian Achille De Giovanni ("Sull'arterite. Sue forme cliniche e sua patogenesi", 1882) and the latter by the French Theophile Guyot ("L'arthritis. Maladie Constitutionnelle", 1890).